Yves Régnier, le bel oublié de la littérature française (2018)
Yves Régnier est le bel oublié de la littérature française. Son oeuvre est pourtant d'une rare qualité. Le temps de la réhabilitation est-il venu ?
Keywords: Nomadisme – Mzab

Quand un Djerbien tire la sonnette d’alarme : Djerba se meurt, lentement et dans l’indifférence totale - Jeriri, Lotfi (tuniscope.com, 2018)
Lotfi Jeriri est journaliste mais il est surtout un Djerbien qui s’inquiète pour son île et qui voudrait voir les hôteliers faire preuve de plus de créativité de prise d’initiative pour sortir l’île de sa torpeur. Voici ce qu’il a écrit :
Keywords: Crises environnementales – Djerba

أشهر رجال الإمبراطورية العُمانية في ترسيخ السيادة السلطانية: وزراء وقضاة وعسكريون في عهد السيد سعيد بن سلطان (صحيفة أثير الإلكترونية, 2018)
أثير – تاريخ عمان إعداد: نصر البوسعيدي لكل دولة عظيمة رجال ذوو بأس بالحكمة والإخلاص شديد، فما بالكم ونحن نتحدث هنا عن أشهر رجال الإمبراطورية العمانية الذين كانوا السند الأقوى للسيد سع…

شخصيات حكمت عمان: الشخصية الخامسة والعشرين: السلطان ثُوَيني بن سعيد بن سلطان البوسعيدي (صحيفة أثير الإلكترونية, 2018)
مسقط – أثير تدرّب على شؤون الحُكم في حياة أبيه السيد سعيد بن سلطان إذ كان ينوب عنه في حُكْمِ مسقط أثناء وجود السلطان سعيد في زنجبار؛ منذ عام 1833م. حكم السلطان ثويني من 1856 إلى 1866م، وذلك …
Keywords: Vie politique – Oman – 1856-1866

From the Jabal Nafusa to Egypt: Notes on Ibadi Manuscripts, Print Culture, and the Buffalo Agency in Cairo (part one) | من جبل نفوسة إلى مصر: ملاحظات حول المخطوطات الإباضية وثقافة الطباعة ووكالة الجاموس في القاهرة (الجزء الأول) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Thanks to the good folks over at Ibadica in Paris, I recently obtained a copy of the printed edition of the first Ibadi newspaper from Cairo, the Nibrās al-mashāriqa wa-‘l-maghāriba (ed. Ṣulṭ…
Keywords: Manuscrits – Le Caire

Sulaymān Bāsha al-Bārūnī: A CV in English | سليمان باشا الباروني: سيرة ذاتية بالإنجليزية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
It’s been a busy semester of classes and I haven’t had much time to write. When I saw one particular document from the British Archives today, however, I decided to make time. The docum…
Keywords: Bārūnī; Sulaymān al- (1870-1940)

الصحفي المناضل: الشيخ سليمان الجادوي 1871-1951 (القومية التونسية, 2018)
الرجل الذي كتب منذ سنة 1906 فأنشأ ثلاث جرائد، غرم و سجن بسببها و
Library Catalog: www.9awmya.tn
Keywords: الجادوي، سليمان (1871-1951)

Oddments from a “Nukkārī” Ibadi Library: the al-Ṣāṭūrī Library in Jerba, Tunisia | بقايا من مكتبة “نكارية”: مكتبة الصاطوري بجزيرة جربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Over the past several years, I have worked with private manuscript collections belonging to families in Jerba, Tunisia. The island is home to several well-known libraries, including those belonging…
Keywords: Bibliothèques – Djerba; Nukkarisme

Intersections between Manuscript and Lithograph Cultures in Private Libraries | التداخلات بين ثقافتَي المخطوطات والطبعات الحجرية في المكتبات الخاصّة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Historians interested in Ibadi and other Arabic manuscripts (including me) often treat manuscripts separately from printed materials in private libraries. But in the second half of the 19th century…
Keywords: Bibliothèques – Djerba

Catalog of Ibadi & Other Arabic Manuscripts at the Association pour la sauvegarde de l’île de Djerba (ASIDJ) | فهرس المخطوطات الإباضية وغيرها من المخطوطات العربية في مكتبة جمعية صيانة جزيرة جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
After a series of short visits beginning in 2014 and ending just this week, I’m delighted to offer a preliminary catalog of Ibadi and other Arabic manuscripts held at the library of the Assoc…
Keywords: Catalogue – Djerba

Destroy a mosque they prayed in… imprison them, and beat them | هدم مسجد كانوا يصلون فيه…سجنهم وضربهم - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
This post comes from a handful of fatwas I ran across in the famous Miʿyār al-Muʿrib of the 15th-century North African scholar Aḥmad al-Wansharīsī (d.914/1508). It turns out that this amazing colle…
Keywords: Polémique wahhabite

Workshop on Ibadi Manuscripts (2019)| ورشة عمل حول المخطوطات الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
I am delighted to announce the call for participants in an upcoming workshop entitled “Ibadi Manuscripts and Manuscript Cultures” to be held from 5-6 April 2019 at Al Akhawayn Universit…
Keywords: Manuscrits

Preserving Endangered Archives in Jerba, Tunisia: The al-Bāsī Family Library | الحفاظ على الأرشيفات المهدّدة في جربة: مكتبة الباسي العائلية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
The Journal of Manuscript Studies (3:1, Spring 2018) has just published a short research annotation by my colleague Dr. Ali Boujdidi and myself, describing our project on the El Bessi (al-Bāsī) fam…
Keywords: Manuscrits – Conservation; Manuscrits – Djerba

New Online Resource for Ibadi and Omani Manuscripts & Newspapers | مرجع جديد للبحث حول المخطوطات الإباضية والجرائد متوفّر في الإنترنت - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
I was delighted to learn this past week of an amazing new collection of digital facsimiles of Ibadi manuscripts and related newspapers from Oman, Zanzibar, and the Mzab published online by the Oman…

Unexpected Connections: Musa Bey Grada, the Ottomans, and the Buffalo Agency | روابط غير متوقعة: موسى بيك قرادة، العثمانيون، ووكالة الجاموس - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
While working on an article on the history of Ibadi manuscripts at the Università degli Studi di Napoli L’Orientale (UNO) in Naples, I ran across an interesting connection between that articl…

وفاة العالم القدير الشيخ سالم بن يعقوب (تين ؤسّان, 2018)
حدث في مثل هذا اليوم 26 يناير 1991 وفاة الشيخ المؤرخ سالم بن محمد بن يعقوب الجربي أحد أهم أعلام المذهب الإباضي المعاصرين في جزيرة جربة كان بدون منازع يملك أكبر مكتبة مخطوطات (إذا إستثنينا البارونية التي هي في الأصل نفوسية) . وولد في قرية غيزن (ربما يكون من أواخر من تحدث بالأمازيغية في هذه …
Library Catalog: agadaz.com Section: الشخصيات
Keywords: Biographies

Upcoming Public Exhibition for al-Bāsī Library Project in Djerba, Tunisa: معرض مكتبة الباسيين في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
It is my pleasure to announce the upcoming public exhibition of “Conserving Endangered Archives in Jerba: the al-Bāsī Family Library Project” in Djerba, Tunisia, taking place this comin…
Keywords: Manuscrits – Djerba

Abū Yazīd Makhlad b. Kaydād, the Jihadist | أبو يزيد مخلد من كيداد، الجهادي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
[تنبيه: الترجمة العربية ستأتي بعد] Ibadis appear in surprising places—including late-20th century Jihadist literature. This post is about an unexpected use of the story of the famous 10th-century I…
Keywords: Ibn Kaydad

Tunisie, retrouvailles séfarades à Djerba - Prevost, Virginie; Derriks, Axel (Mondafrique, 2018)
Tunisie, Djerba. Les juifs célébreront Lag Ba Omer le 3 mai et se rassembleront pour le pèlerinage de la Ghriba. Les juifs de Tunisie et du monde entier
Library Catalog: mondafrique.com
Keywords: Judaïsme – Djerba

ندوة علمية حول موضوع جهود الشيخين الحاج محمد نوح مفنون والحاج محمد ابصير (موقع مجلس أعيان آت يسجن, 2018)
الحاج محمد بن بنوح نوح مفنون والحاج محمد بن عمر ابصير وجهادهما " المجتمع بين الوفاء للمبادئ والتعامل مع التحديات " موضوع ندوة علمية تحت إشراف حلقة العزابة

Une si longue Antiquité tardive : À propos des derniers chrétiens d’Afrique du Nord médiévale - Nsiri, Mohamed Arbi (Carnet de recherche de l'IPRA, 2018)
Le Maghreb est aujourd’hui une région qui revendique, à juste titre, sa double appartenance à la communauté musulmane et au monde arabe. Or cette région, après bien des vicissitudes, est pris la lointaine succession d’une Africa qui, depuis la chute de la Carthage punique, appartenait aussi sûrement au monde romain puis au monde chrétien. Comment donc expliquer cette métamorphose culturelle,...
Keywords: Christianisme – Afrique du nord

Ibadi Shamelessly Defends Haruriya Kharijites (2018)

Comment vivent les derniers juifs de Djerba? - Cheslow, Daniella (JForum, 2018)
Djerba, l’avenir de l’une des dernières et plus anciennes communautés juives du monde arabe est incertain
Keywords: Judaïsme – Djerba